2015
DOI: 10.1186/s12889-015-2058-x
|View full text |Cite
|
Sign up to set email alerts
|

Double-burden of malnutrition among the indigenous peoples (Orang Asli) of Peninsular Malaysia

Abstract: BackgroundDouble-burden of malnutrition (DBM) is an emerging public health concern among the Orang Asli (indigenous peoples) of Peninsular Malaysia. This study aimed to identify the presence of DBM at the community and household levels in Orang Asli population and its associated demographic and socio-economic factors.MethodsThis cross-sectional study was conducted in 11 Orang Asli villages surrounding the Krau Wildlife Reserve, Peninsular of Malaysia from October 2011 to January 2012. Of 438 households, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
81
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 26 publications
14
81
2
Order By: Relevance
“…Our results revealed that mothers who were above 35 years were found to be at higher risk of double burden of malnutrition. This result is consistent with Emdadul et al, and Wong et al, who suggested that the prevalence of overweight/obesity was higher in older age groups compared to younger groups [3,35].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results revealed that mothers who were above 35 years were found to be at higher risk of double burden of malnutrition. This result is consistent with Emdadul et al, and Wong et al, who suggested that the prevalence of overweight/obesity was higher in older age groups compared to younger groups [3,35].…”
Section: Discussionsupporting
confidence: 92%
“…Malnourished mothesr are more likely to have a low birth weight baby which signifies the importance of exploring the double burden of malnutrition among mother-child pairs. [19,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Childhood undernutrition is a persistent health problem in the Orang Asli population that has been documented over the decades at levels that are much higher than those reported in other rural or poor communities in Malaysia. Studies reported that child undernutrition remains relatively high (43-86%) with stunting being more prevalent than underweight [31][32][33][34][35][36][37][38]. Anaemia indicative of iron deficiency and helminthic infestation is also an age-old nutritional problem affecting the Orang Asli [5].…”
Section: Studies On Orang Asli Health Food and Nutrition Securitymentioning
confidence: 99%